Underinvestment and value relevance of earnings management - Mohamat Sabri Hassan,; Norman Mohd Saleh,; Aulia Fuad Rahman,; Zaleha Abdul Shukor, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The aim of this study is to examine whether earnings management among underinvestment firms is positively related to share price. Firms are said to have high growth opportunity but is unable to fund investment projects due to liquidity constraints because of the information asymmetry between the firm and the investors. As a result, firms have to provide high quality accounting information (i.e. value relevant information) to reduce information asymmetry and hence be free from liquidity constraints. One type of accounting information that can be provided is discretionary accrual (proxy for earnings management). The sample of this study is firms listed on the Main Board of Bursa Malaysia from year 2001 to 2007. We use Ohlson’s model to examine the value relevance of earnings management. We separate earnings into managed and unmanaged earnings. Panel data regression analyses were performed to examine the role of underinvestment on the relationship between earnings management and share price. We also examine the value relevance of earnings management using the return model. The results from the panel data regression analysis indicate that earnings management increases the value relevance of accounting information. Further, underinvestment moderates the relationship between earnings management and share price. Nevertheless, the results suggest that earnings management among firms can decrease the value relevance of accounting information. In general, it is concluded that underinvestment weakens the relationship between earnings management and share price/return, hence it motivates managers to convey opportunistic earnings management.